FARMER’S KNOWLEDGE AND PERCEPTION OF INTEGRATING PHOSPHORUS FERTILIZER AND MULCHES IN COWPEA PRODUCTION - Ashwini A (Global Journal of Plant and Soil Sciences, 2024)
Cowpea (Vigna unguiculata (L.) [Walp] is increasingly sought for its high nutritional content, climate resilience, and ecological function in improving soil fertility. Cowpea production is hindered by an array of biotic and abiotic factors, such as pests, drought, low soil fertility, notably phosphorous (P), and farmers’ limited knowledge of the importance of mulching and phosphorous application. A survey was done between September 2022-April 2023 to determine the available cowpea management techniques and assess farmer’s knowledge and perception of integrating mulches and phosphorous fertiliser cowpea production in Karingani Ward, Chuka Sub-County, Tharaka-Nithi County. Data collected was analyzed using Statistical Packages for Social Scientists (SPSS) software version 21.0. Frequencies and percentages present descriptive statistics, while the Binary logistic model measured the relationship between the categorical target variable and the independent variables. The study findings showed that cowpea farming is dominated by males (60%) of aged 40-60 (53%), and most 50% attained the primary level of education. Most farmers 83% are small farm-holders relying on rainfed farming, of which long rain occurs between March and June, and short rain is received from August and December with 91% response rate. The cowpea variety M66was the most preferred indicated by 60% response rate for sale and consumption and most farmers 85% obtained planting seeds from the previous harvest. Drought, low soil fertility, and some pests were found as the key cowpea production constraints. Further, most farmers59% applied NPK during planting and they conquered that phosphorous fertilizer is an essential macronutrient in cowpea production. However, it was found that most 71% apply inappropriate amounts of fertilizers as they depend on visual estimation. The findings are crucial for developing ways to increase cowpea yield among smallholder growers, particularly in Tharakanithi County, where subsistence farming is common. Increased cowpea production through proper use of inputs such as P fertilizers and mulching could potentially assist Kenya reduce its enormous imports of cowpea grain from neighboring nations. The study also found that P-containing fertilizers integrated with plastic mulch are critical production inputs for increasing cowpea output in the region and in places with similar traditional farming practices. The study will benefit breeders, development partners, extension personnel, and other stakeholders in cowpea value chains. The study recommends that both genders and youths to actively participate in cowpea farming and farmers should be provided with extension services to boost their farming knowledge.